2008
DOI: 10.1152/ajpendo.90257.2008
|View full text |Cite
|
Sign up to set email alerts
|

Pair feeding-mediated changes in metabolism: stress response and pathophysiology in insulin-resistant, atherosclerosis-prone JCR:LA-cp rats

Abstract: Russell JC, Proctor SD, Kelly SE, Brindley DN. Pair feedingmediated changes in metabolism: stress response and pathophysiology in insulin-resistant, atherosclerosis-prone JCR:LA-cp rats. Am J Physiol Endocrinol Metab 294: E1078-E1087, 2008. First published April 15, 2008 doi:10.1152/ajpendo.90257.2008.-Rats of the JCR: LA-cp strain, which are homozygous for the cp gene (cp/cp), are obese, insulin-resistant, and hyperinsulinemic. They exhibit associated micro-and macrovascular disease and end-stage ischemic my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The exercise-dietary energy restriction intervention commenced when animals were 3 weeks old (at weaning) and ended when animals were 11 weeks of age (before adulthood), suggesting that early intervention when compared to late intervention (Diane et al 2013b) is more effective in terms of reproductive improvements in this obese PCOS-prone model. Also, compared to previous studies from our group and others, the findings from this current study showed that the combination of energy restriction and voluntary exercise mediates beneficial effects on metabolic and reproductive outcomes in this obese PCOS-prone rodent model compared to dietary energy restriction alone (Bronson 1987, Russell et al 2008, Diane et al 2013a. Our findings that plasma total testosterone, FAI and ovarian follicular morphology were not statistically different between experimental groups are a reflection of the use of younger animals in this PCOSprone model, as these animals do not display the full PCOS phenotype until adulthood (O12 weeks) (Shi et al 2009).…”
Section: Hypothalamic Arc Neuropeptide and Peptide Expressionsupporting
confidence: 49%
See 1 more Smart Citation
“…The exercise-dietary energy restriction intervention commenced when animals were 3 weeks old (at weaning) and ended when animals were 11 weeks of age (before adulthood), suggesting that early intervention when compared to late intervention (Diane et al 2013b) is more effective in terms of reproductive improvements in this obese PCOS-prone model. Also, compared to previous studies from our group and others, the findings from this current study showed that the combination of energy restriction and voluntary exercise mediates beneficial effects on metabolic and reproductive outcomes in this obese PCOS-prone rodent model compared to dietary energy restriction alone (Bronson 1987, Russell et al 2008, Diane et al 2013a. Our findings that plasma total testosterone, FAI and ovarian follicular morphology were not statistically different between experimental groups are a reflection of the use of younger animals in this PCOSprone model, as these animals do not display the full PCOS phenotype until adulthood (O12 weeks) (Shi et al 2009).…”
Section: Hypothalamic Arc Neuropeptide and Peptide Expressionsupporting
confidence: 49%
“…The FF-Sedentary or Lean-Control groups were also placed in the wheel running apparatus for 4 h/day but the wheels were locked. Previous data from our group has shown that dietary early energy caloric restriction plus sedentary behaviour without exercise significantly improves cardiometabolic parameters in young animals in this rodent model (Russell et al 2008, Diane et al 2013a. Therefore, in this study a dietary ER-Sedentary group was not included, as the aim was to compare the effect of exercise under free feeding and dietary energy restriction conditions.…”
Section: Exercise and Energy-restriction Diet Protocolmentioning
confidence: 77%
“…Body weight and circulating levels of insulin and leptin were reduced relative to the untreated obese animals, but were still elevated compared with the lean controls, in agreement with previous reports (18,19). In earlier studies, the pairing of obese rat food intake to control animals and the feeding of benfluorex or d -fenfluramine have been found to diminish cardiovascular disease and myocardial lesions in this corpulent rat model (14,18,19,34,35). Ad libitum feed consumption in benfluorex-treated obese rats was comparable to the intake of their lean control counterparts, which was mirrored by a low aortic neovascular MR signal in both groups of animals.…”
Section: Discussionmentioning
confidence: 81%
“…In this regard, previous studies with pair-fed obese type 2 diabetic rodents have shown that a reduction in food intake contributes to ~53% of the antihyperglycemic effect of liraglutide (a long-acting glucagon-like peptide-1 derivative) [68]. It is noteworthy that on an unrestricted diet, the obese, insulin-resistant rodents (that are also hyperphagic) consume food throughout the 24-h cycle [69,70]. In contrast, on a restricted diet (pair-fed condition), the obese rodents consume all food within 3 to 10 h that would result in fasting or caloric deprivation for the remaining period in the 24-h cycle [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that on an unrestricted diet, the obese, insulin-resistant rodents (that are also hyperphagic) consume food throughout the 24-h cycle [69,70]. In contrast, on a restricted diet (pair-fed condition), the obese rodents consume all food within 3 to 10 h that would result in fasting or caloric deprivation for the remaining period in the 24-h cycle [69,70]. In the present study with type 2 diabetic db/db mice (obese/hyperphagic), we thus avoided pair-feeding and also for the reason that db/db mice were subjected to 4h fasting periods for blood sample collections to measure glucose and βOHB levels (on days 1, 3, 5, 7 and 9) and to perform GGT test (on day 5) during the 9-day treatment protocol.…”
Section: Discussionmentioning
confidence: 99%